LEXICO-SEMANTIC STUDY OF ACCOUNTING AND AUDIT TERMS (Scientific journal of the Fergana State University, 2024)
In this article, we tried to determine the morphological classification, lexical-semantic properties, functional-semantic properties of terms and lexemes in the study of accounting and audit terminology, as well as to determine which word groups they belong to when describing term systems in modern linguistics.